Hospitalization following eating disorder diagnosis: The buffering effect of marriage and childbearing events - Jennifer Tabler; Rebecca L. Utz (Elsevier, 2020)
Eating Disorders (ED) are defined as abnormal eating behaviors, stemming from an obsession with food, body weight, or body shape. EDs affect 10 million men and 20 million women in the US, with an estimated 15% lifetime prevalence among women. An ED diagnosis is often accompanied with a host of adverse physical and mental health outcomes, including a heightened risk for suicidality. Given the complex comorbidities associated with EDs, treatment occurs in inpatient and outpatient settings. This study used linked administrative and health records from the Utah Population Database to create a cohort of women n = 4183 and men n = 423 who had a known diagnosis of ED between 1995 and 2015. Cox proportional hazard regression was used to model ED-related hospitalization trajectories, including subsequent risk for suicidality/self-injurious behavior-related hospitalization. To better estimate the risk profiles associated with different health care utilization patterns, models explored how family-related life course events (childbirth, marriage transitions) and sociodemographic characteristics (race, sex, and median income at census-block) modify hospitalization trajectories following initial diagnosis. Results suggested that increased outpatient treatment was associated with reduced risk of initial ED-related hospitalization, but higher risk for subsequent ED-related hospital readmission. In addition, transition to marriage (i.e., getting married) was associated with reduced risk of ED-related and suicidality/self-injurious behavior-related hospitalizations (initial hospitalization and subsequent readmission). Increased number of children was only associated with reduced risk of initial ED-hospitalization, but not readmission. When assessing individuals' risk for ED-related hospitalizations, social and health services researchers should contextualize treatment trajectories within the individual's life experiences, particularly marital transitions, while simultaneously considering sociodemographic characteristics and utilization of outpatient care. Future research should further examine whether marriage represents an important turning point in the health trajectories of individuals with EDs.